Mexiletine in the treatment of LQT2, LQT3, and acquired LQTS: a meta-analysis - Dhiya Ihsan; Mohammad Iqbal; Charlotte Johanna Cool; Chaerul Achmad; Miftah Pramudyo; Hawani Sasmaya Prameswari; Mohammad Rizki Akbar (The Indonesian Heart Association, 2025)
Background: High mortality in patients with Long QT Syndrome (LQTS) can be reduced with proper treatment. Gene-specific therapy is crucial, as many treatments are not equally effective across different LQTS types. While mexiletine has been established in the treatment of LQT3, its use in other types of LQT need further evaluation. Methods: A meta-analysis was conducted using systematic electronic searches of PubMed, Embase, and Cochrane Library. We assessed QTc reduction and cardiac events after Mexiletine treatment. Inclusion criteria: any study with no language restriction that diagnoses any type of LQTS, uses mexiletine treatment, and provides QTc comparison before and after treatment. Animal studies were excluded. The NIH Study Quality Assessment Tools and Newcastle-Ottawa Scale were used to evaluate bias. Data were analyzed using Review Manager 5.4 and MedCalc software Results: Nine studies (n=281) were included. Mexiletine reduced QTc by -64ms (mean difference [MD], -64.22; 95% confidence interval [CI] -76.13 to -52.30; p<.001; I2 60%). Sensitivity and subanalyses showed consistent efficacy. In five studies (n=76), the number of patient with high-risk QTc (>500ms) significantly decreased (Risk Ratio [RR], 0.38; 95% CI 0.26-0.55; p<.001). Five studies (n=141) showed a significant reduction in cardiac events (RR, 0.25; 95% CI 0.14-0.44; p<.001). Two studies reported gastrointestinal (GI) problems and vertigo as side effects of mexiletine treatment. Conclusion: Mexiletine significantly reduces QTc and cardiac events in LQT2, LQT3, and aLQT patients. Mexiletine also significantly reduces the number of Long QT patients with high-risk QTc Funding: No external funding was received for this study Registration: CRD420250652574